A postcolonial critique of John Warneck and the Batak religious identity - Bonnarty Steven Silalahi (Institut Agama Kristen Negeri Toraja, 2026)
This study examines Johannes Warneck’s theological and anthropological interpretation of Batak indigenous religion as heathenism within the broader framework of colonial mission discourse. The research aims to evaluate whether Warneck’s category of heathenism adequately represents Batak religious identity or instead distorts it through a theological-civilizational hierarchy. Methodologically, the study employs qualitative textual analysis of Warneck’s The Living Christ and Dying Heathenism, read through a postcolonial hermeneutical lens and compared with historical and ethnographic scholarship on Batak religion, cosmology, and customary law. Theoretically, the study engages with postcolonial criticism and biblical models of contextualization, especially Acts 15 and Acts 17, to assess the relationship between Gospel proclamation and local culture. The findings show that Warneck construed Batak religion as estrangement from God, bondage to spirits, moral deficiency, and spiritual degeneration, while Batak society in fact possessed coherent religious concepts, ritual structures, and customary legal institutions. The study concludes that a contextual and redemptive missiology offers a more adequate framework, one that preserves Christian theological conviction while taking local identity and cultural forms seriously.